Motivating reading comprehension : concept-oriented reading instruction - Guthrie, John T.; Wigfield, Allan; Perencevich, Kathleen C. (L. Erlbaum Associates, 2004)
This text discusses motivating reading comprehension covering subjects such as classroom contexts for engaged reading, scaffolding for motivation and engagement in reading, the cognitive strategies of reading comprehension and science inquiry in the CORI framework.